The land of stories beyond the kingdoms - Colfer, Chris (The land of stories, 2017)
The Masked Man is on the loose in the Land of Stories, and it's up to Alex and Conner Bailey to stop him except Alex has been thrown off the Fairy Council, and no one will believe they're in danger. With only the help of the ragtag group of Goldilocks, Jack, Red Riding Hood, and Mother Goose and her gander, Lester, the Bailey twins discover the Masked Man's secret scheme: He possesses a powerful magic potion that turns every book it touches into a portal, and he is recruiting an army of literature's greatest villains!